JURGEN HABERMAS'S COMMUNICATIVE PARADIGM AS TRANSFORMATIVE DA'WAH REINFORCEMENT - Saputra, Dani (UIN Kiai Ageng Muhammad Besari Ponorogo, 2021)
Work and communication are two basic human that determine how humans as a species move and live in their world. The reformation begins with two basic human foundations. Jurgen Habermas, a German authoritarian who makes a fairly firm discount with his predecessors, seems to be in his central idea of the fundamental differences between the two dimensional praxis, namely work and communication. But it needs to be seen how communication and rationality of power are exercised, or how one positions in it. In the public space, each individual expresses his or her various thoughts related to the public interest that want to be discussed without coercion. This public space must be free from the intervention of any party, so that each individual can express his or her thoughts freely and openly. That's where a social area free from censorship and dominance. The complexity of people’s lives demands a more transformative movement of da’wah activities, in this case communication and transformative da’wah. This process also aims to